Spray Gel Formulation of Ethanolic Extract Senduduk Leaves (Melastoma malabatricum) Against Antioxidant Activity, SPF, and Chemical Components Analysis with LC-MS/MS - Yulion, Rizky; Andriani, Lili; Asadi, Henityo Agung; 'Aliyah, Siti Hamidatul; Mariska, Ruri Putri; Perawati, Santi; Hasanah, Rifdatul (Indonesian Scholar Society, 2023)
Senduduk leave (Melastoma malabathricum) is one of the species in the melastomaceae family that has long been used by local Indonesian people, one of which is the Suku Anak Dalam (SAD) for various needs and also as traditional medicine. The study aimed to examine the antioxidant activity of ethanolic extract of senduduk leaves. The extract was then formulated into spray gel preparations as UV-B sunscreen. The research method used was starting from sampling, determination, making samples, soxhlet, determining the IC50 value, spray gel preparation formulation, formulation stability test, measuring sun protection factor (SPF) values, and identifying extract chemical components with the LC-MS/MS instrument. The results was that the ethanolic extract of senduduk leaves had an IC50 value of 49.73 μg/mL with the best SPF value at a concentration of 70 ppm, which is 19.98. Spray gel preparations with a concentration of 70 ppm have an IC50 value of 44.22 μg/mL, an SPF value of 24.96, and a potent antioxidant intensity. So, extract spray gel can potentially have activity as antioxidants and can be used as UV-B sunscreen. The compounds identified include quercetin, quercitrin, DEET, n-boc-3-pyrrolidinone, medicarpine, taxinine, and other compounds. The ethanol extract of the soxhlet results showed more promising results for further tests of in-vitro, in-vivo, and in-silico bioactivity studies.